A one-pot method for the synthesis of phenylalkynyl-substituted terminal alkynes by deprotection/stannylation followed by a Migita–Kosugi–Stille coupling. (1st June 2018) - Peng, Li-Fen; Wang, Bing-Hao; Wang, Ming; Tang, Zi-Long; Jiang, Yan-Zi; Jiao, Yin-Chun; Xu, Xin-Hua
A practical one-pot approach for the synthesis of arylalkynyl-substituted terminal alkynes has been developed through a deprotection/stannylation of a phenylethynyl phosphine oxide followed by Migita–Kosugi–Stille coupling, avoiding the longer synthetic route involving repeated deprotection/Sonogashira coupling. Other features of this approach include mild reaction conditions, excellent yields, facile isolation of products and wide functional group tolerance.